Electrophysiological Assessment of Essential Tremors’ Severity by accelerometer: Frequency Domain Approach - Ameer, Abdulnasir Hussien; Park, Byung Rim; Ouraiby, Alaa (AL-Kindy College Medical Journal, 2024)
Background: Evaluation of tremors is critical in the management of essential tremors, starting from early diagnosis to initial medication and follow-up. Clinical rating scales, accelerometry, or electrophysiology can be used to determine the severity of tremors. However, clinical assessments are self-administered and may be influenced by intra- and inter-evaluator differences in experience and small changes in tremor severity. Objectives: to demonstrate whether accelerometers are a valuable method for assessing patients with essential tremors. Subjects and Methods: In the postural position, hand tremor was recorded using a unidirectional piezoelectric accelerometer placed on the dorsum of the index finger for 60 seconds. Fourier (spectral) analysis was used to determine the amplitude and frequency of the tremors. Results: Significant correlations between log tremor amplitude and the Essential Tremor Rating and Assessment Scale were found. Conclusions: unidirectional piezoelectric accelerometers can be used to objectively assess the intensity of essential tremors on routine basis, which may aid in treatment adjustment.